2005
DOI: 10.1124/jpet.105.089482
|View full text |Cite
|
Sign up to set email alerts
|

Niemann-Pick C1 Protein Facilitates the Efflux of the Anticancer Drug Daunorubicin from Cells According to a Novel Vesicle-Mediated Pathway

Abstract: Niemann-Pick C1 (NPC1) is a late endosomal/lysosomal membrane protein originally reported on for its role in cholesterol trafficking in mammalian cells. NPC1 has been shown recently to share significant structural homology with a family of prokaryotic permeases and was proposed to play a role in intracellular drug transport; however, the mechanism for this has not been fully understood. We provide evidence here that is consistent with NPC1's involvement in a vesicle-mediated clearance of the anticancer agent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 18 publications
1
36
0
Order By: Relevance
“…For example, the accumulation of a lysosomotropic drug in lysosomes of fibroblasts from NPC1 patients was greater than from normal subjects (28). Substantial amounts of endogenous hydrophobic amines such as sphingosine are concentrated in the lysosomes of liver from mice with NPC disease (26), and Lloyd-Evans et al (32) demonstrated that sphingosine accumulation in lysosomes is an initiating factor in NPC1 disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the accumulation of a lysosomotropic drug in lysosomes of fibroblasts from NPC1 patients was greater than from normal subjects (28). Substantial amounts of endogenous hydrophobic amines such as sphingosine are concentrated in the lysosomes of liver from mice with NPC disease (26), and Lloyd-Evans et al (32) demonstrated that sphingosine accumulation in lysosomes is an initiating factor in NPC1 disease pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This may be relevant for MCF-7TaxR where we see a hypopolarised state in spite of the presence of P-gp. The influence of a reduced plasma membrane potential and /or the reduced cytoplasmic conductivity (as [26] and the possibility of altered pH gradients with respect to the parent line [32]. A report by Raghunand et al [33] reported that an acidic pH may enhance microtubular stabilization by paclitaxel [34].…”
Section: Discussionmentioning
confidence: 99%
“…While the complete physiological function of NPC1 is still unclear, NPC1 does share homology with the resistance-nodulation-division family of prokaryotic permeases and may function as a transmembrane efflux pump to transport cargos in LEs (9,75). Other studies suggest that NPC1 might also function in vesicle-mediated pathways for cargo transportation from LEs to other intracellular sites (21,33). Recent studies by Infante et al have propelled forward our understanding of how NPC1 works together with NPC2, also known to bind cholesterol, to support cholesterol efflux from the LE (32).…”
mentioning
confidence: 99%